Aberrant expression of corticotropin-releasing hormone in pre-eclampsia induces expression of FasL in maternal macrophages and extravillous trophoblast apoptosis - Petsas, George; Toth, Bettina (Molecular human reproduction, 2012)
Abstract. Corticotropin-releasing hormone (CRH) and its receptors are expressed in human placenta. Recently, the impaired function of this system has been asso